Mesenchymal stem cells therapy improves ovarian function in premature ovarian failure: a systematic review and meta-analysis based on preclinical studies - Guo, Congcong; Ma, Yubo; Situ, Yanqiu; Liu, Li; Luo, Guoqun; Li, Huan; Ma, Wenmin; Sun, Li; Wang, Wen; Weng, Qiuying; Wu, Linlin; Fan, Dazhi (Frontiers in Endocrinology, 2023)
Background: Studies reveal that mesenchymal stem cells (MSCs) transplantation might be a potential star candidate for premature ovarian failure (POF) in animal experiments. However, individual studies with a small sample size cannot be used to draw a clear conclusion. Therefore, we conducted a systematic review and meta-analysis to explore the potential of using MSCs in the treatment of POF animals. Methods: Seven databases were searched for studies exploring MSCs transplantation on POF in animal model. The PRISMA guideline was followed, and the methodological quality applied to SYPCLE’s risk of bias tool. RevMan 5.4 and STATA 12.0 software was performed to meta-analysis. Results: Thirty-seven studies involving 1079 animals were included. Significant associations were found for MSCs with the levels of E2 (SMD 2.69 [95% CI 1.97, 3.41]), FSH (-2.02, [-2.74, -1.30]), primary follicles (2.04, [1.17, 2.92]), secondary follicles (1.93, [1.05, 2.81]), and primordial follicles (2.38, [1.19, 3.57]. Other outcomes, such as AMH, LH, INHB, antral follicles, growing follicles, mature follicles, and early antral were also found significantly. There was no difference in FSH/LH, corpus leteum, follicles, and estruc cycle. Conclusions: Our meta-analysis result indicated that MSCs transplantation might exert therapeutic effects on animal models of POF, and these effects might be associated with the improving the disorder of sexual cycle, modulating the serum hormone expression to a better state and restoring ovarian function.